Sobrevivência de Xanthomonas campestris pv. campestris no solo, no filoplano e na rizosfera de plantas daninhas - Silva, João César da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Black rot, incited by Xanthomonas campestris pv. campestris (Xcc), is the most destructive bacterial disease of brassicas in many countries, and can promote substantial reductions in productivity. The study of survival ecological niches of phytopathogenic bacteria has great importance in the management of plant bacteriosis, since a small amount of inoculum surviving among the cultivation cycle may be sufficient to initiate a new outbreak in the field. Based on this, this study evaluated the survival of Xcc in different experiments using Xcc strain 3098C, resistant to 100 μg/mL of rifampicin. The survival of Xcc as free cells in the soil was evaluated in five experiments, carried out in field conditions, between May and August, 2014. Under controlled conditions, six types of soil were used, sampled from different areas, with or without brassicas cultivation. The colonization of phylloplane and rhizosphere of 26 weed species by Xcc was also evaluated in field experiments, between August, 2014 and October, 2015. In field experiments, Xcc survived between 4 and 7 days in the soil, being directly influenced by temperature and humidity that occurred during the experiments. Under controlled conditions, the bacteria survived for 10 to 24 days, and these periods were influenced by texture, pH and organic matter content in each soil type. In weeds rhizosphere, Xcc had low capacity to survive, at most 28 days on Raphanus raphanistrum. In phylloplane, Xcc survived more than 42 days in Lepidium virginicum, and up to 70 days in Raphanus raphanistrum. Weeds from Amaranthaceae and Poaceae families did not show potential for the epiphytic survival of Xcc.

A podridão negra, incitada por Xanthomonas campestris pv. campestris (Xcc), é considerada a doença bacteriana mais destrutiva das brássicas em muitos países, podendo promover consideráveis reduções na produtividade. O estudo dos nichos ecológicos de sobrevivência de bactérias fitopatogênicas possui grande importância no manejo de fitobacterioses, uma vez que uma pequena quantidade de inóculo sobrevivente entre os ciclos de cultivo pode ser suficiente para iniciar uma nova epidemia no campo. Baseado nisso, o presente trabalho avaliou a sobrevivência de Xcc em diferentes ensaios, através da utilização do isolado 3098C de Xcc resistente a 100 μg/mL de rifampicina. A sobrevivência de Xcc na forma de células livres no solo foi avaliada em cinco experimentos, desenvolvidos em condições de campo, entre maio e agosto de 2014. Em condições controladas¸ foram utilizados seis tipos de solo, amostrados de diferentes áreas com cultivo ou não de brássicas. A colonização do filoplano e rizosfera de 26 espécies de plantas daninhas por Xcc também foi avaliada em experimentos de campo, entre agosto de 2014 a outubro de 2015. Nos experimentos de campo, Xcc sobreviveu entre 4 e 7 dias no solo, sendo influenciada diretamente pela temperatura e umidade, ocorridas durante os experimentos. Em condições controladas, a bactéria sobreviveu de 10 a 24 dias, sendo esses períodos influenciados pela textura, pH e teor de matéria orgânica em cada tipo de ...
Survival of xanthomonas campestris pv. campestris in soil, phylloplane and rhizosphere of weeds
Keywords: Xanthomonas campestris; Plantas invasoras; Solos; Bactérias; Bacteria